1996
DOI: 10.1038/nsb0796-638
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial chitobiase structure provides insight into catalytic mechanism and the basis of Tay–Sachs disease

Abstract: Chitin, the second most abundant polysaccharide on earth, is degraded by chitinases and chitobiases. The structure of Serratia marcescens chitobiase has been refined at 1.9 A resolution. The mature protein is folded into four domains and its active site is situated at the C-terminal end of the central (beta alpha)8-barrel. Based on the structure of the complex with the substrate disaccharide chitobiose, we propose an acid-base reaction mechanism, in which only one protein carboxylate acts as catalytic acid, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
361
3
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(381 citation statements)
references
References 57 publications
13
361
3
4
Order By: Relevance
“…Tews et al have reported that S. marcescens NAG uses an acid-base reaction mechanism with glutamic acid 540 as the catalytic amino acid. 12) This residue is well conserved in all members of family 20 of glycosyl hydrolases (Fig. 5).…”
Section: Isolation Of the Gene Coding For Nag20a And Sequence Analysismentioning
confidence: 99%
“…Tews et al have reported that S. marcescens NAG uses an acid-base reaction mechanism with glutamic acid 540 as the catalytic amino acid. 12) This residue is well conserved in all members of family 20 of glycosyl hydrolases (Fig. 5).…”
Section: Isolation Of the Gene Coding For Nag20a And Sequence Analysismentioning
confidence: 99%
“…Structural studies of N-acetyl-b-glucosaminidases from families GH3, 16 GH20, 20,21,24,25 and GH84 22,26 have revealed significant differences in the active site structures of enzymes carrying out substrate assisted catalysis versus those proceeding via a glycosyl-enzyme intermediate. For GH3 enzymes, it has been found that the 2-acetamido group of the substrate is not essential for cleavage of the glycosidic bond, consistent with these enzymes using an enzymic nucleophile.…”
mentioning
confidence: 99%
“…Although GH3 enzymes, including NagZ, are functionally related to the GH20 human b-hexosaminidase isoenzymes and GH84 O-GlcNAcase, recent kinetic [17][18][19] and structural studies 16,[20][21][22] have revealed that GH3 enzymes use a catalytic mechanism that differs from that used by GH20 and GH84 enzymes. This distinction should therefore offer a tractable route to generating selective inhibitors of NagZ, and clear comparisons of these enzymes at a structural level would greatly accelerate these efforts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alignment of the amino acid sequence of these ␤-hexosaminidases is shown in Figure 2. All of the residues, which are thought to form the active site of the subunits, suggested either from analyses of mutant human proteins (Brown & Mahuran 1991;Liessem et al 1995;Tse et al 1996;Fernandes et al 1997) or from structural analysis of a member of the glycosyl hydrolase family 20 (Serratia marcescens chitobiase; Tews et al 1996), are conserved in P. mammillata. We found five potential N-glycosylation sites in the P. mammillata ␤-hexosaminidase.…”
Section: Fig 2 Multiple Alignment Ofmentioning
confidence: 99%